Chasing the Literature Phenomenon : A Plastic and Technical Perspective of the Text (Imaginations: Journal of Cross-Cultural Image Studies, 2023)
The following reflection proposes to shift the perspective on literary matters by reexamining the question of the ontology of literature based on the materiality of the text (its technical, media, and editorial arrangements). The identification of the phenomenon of literature, an ongoing issue in literature over the ages (up to digital literature), raises questions about the realities of a number of categories (readable, visible, audible) and systems of antinomy (substance/form, matter/meaning), opening up a much wider discussion of matter in the world. By studying a number of intellectual approaches that investigate porosities between medium and inscription (the theories of media studies and the new materialism) and a number of creations that enhance the medial part of the text (Balzac’s Physiologie du mariage, Mallarmé’s Un Coup de dés jamais n’abolira le hasard and Carson’s Nox), the article seeks to dismantle the essence of the phenomenon of literature into a diversity of agencies and a multitude of plastic practices.